Too Much Too Soon: Instability and Indeterminacy with Forward-Looking Rules - Nicoletta Batini; Joseph Pearlman (Bank of England, External Monetary Policy Committee Unit, 2002)
This paper extends the existing literature on the uniqueness and stability conditions for an equilibrium under inflation-forecast-based (IFB) rules. It shows that, for a variety of New Keynesian sticky-price and sticky-inflation models, these are a function not just of the degree of responsiveness of the policy instrument to deviations of expected inflation at some horizon j from target, but rather of the 'right' combination of that degree and the chosen feedback horizon. In this respect we prove analytically that the determinacy results in Clarida et al (2000) cannot be generalised to the case of IFB rules with longer feedback horizons than one quarter. The paper shows how to identify the feedback/horizon pairs that are associated with unique and stable equilibria and unveils the analytical rationale behind instability or indeterminacy at too long a lag for a given feedback.
Keywords: 330